CHANGES IN PERINEURIAL AND HEMATOENDONEURIAL BARRIERS OF THE SCIATIC NERVE IN PACLITAXEL-INDUCED PERIPHERAL NEUROPATHY - Gevka, O.I. (World of Medicine and Biology, 2017)
The absence of a unified concept of paclitaxel-induced peripheral neuropathy morphogenesis determines the need for a detailed morphological study. This paper demonstrates ultramicroscopic changes in the structure of the perineurial and the hematoendoneurial barriers of the sciatic nerve in albino rats caused by paclitaxel. Chemotherapeutic agent was administered intraperitoneally at a dose of 2 mg/kg of body weight, each alternate day, 4 times. The experiment period was 120 days; during the experiment, samples were collected for morphometric study and electron microscopic study. In the experiment, there were determined changes in endoneurial blood flow manifested themselves as congestion, morphological signs of transendothelial transport abnormalities, dystrophic changes in endothelial cells of varying severity and stages, thickening and dissociation of the basement membrane. In the perineurium, the disorganization of fiber and cellular elements, deformation of the processes, hydropic dystrophy of perineurial cells and impaired permeability of the perineurium progressing within the first months of the experiment and gradually disappearing until the end of the experiment were observed.
Keywords: Paclitaxel; perineurial barrier; hematoendoneurial barrier; peripheral neuropathy